On the Role of EFL/ESL Teachers' Emotion Regulation in Students' Academic Engagement - Wang, Fang; Ye, Zhi (Frontiers in Psychology, 2021)
Considering the pivotal role of students’ academic engagement in their success, discovering the intrinsic and extrinsic factors that inspire students to engage in class activities seems crucial. Notwithstanding, only a few empirical studies have been devoted to teachers’ personal factors such as emotion regulation and their predictive function. Further, to our knowledge, no theoretical or systematic review study has been conducted on the association between teacher emotion regulation and student academic engagement. The current review study seeks to fill these lacunas by illustrating English as a foreign language (EFL) or English as a second language (ESL) teachers’ emotion regulation and its’ capability to enhance students’ academic engagement. Using the existing evidence, the power of ESL/EFL teachers’ emotion regulation in predicting their pupils’ academic engagement was proved. The findings' educational implications are further discussed.